Effectiveness of Health Education-oriented Program on Parents' Awareness towards Adolescents' Violence Control in Baghdad City - Sajem, Kareem; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2010)
Objective: This study aims to determine the effectiveness of health education oriented program on parents' awarenesstowards adolescents' violence control.Methodology: A quasi-experimental study was carried out in Baghdad city form 1st of April, 2008 to 1st of September,2009. A purposive "non-probability" sample of 60 parents who have adolescents' violence in their families who wereselected according to specific criteria. The researcher divided the samples into two equal groups; the study and controlgroups. The health education program, as well as a questionnaire was constructed as tools for data collection by theresearcher for the purpose of the study. Content validity was determined by a panel of experts in different specialties.Reliability of instrument was determined by the use of test-retest approach through the pilot study which was carriedout from October, 1st, 2008 to October, 22nd, 2008. Data were analyzed through the application of the descriptivestatistics (frequency, percentage and mean), and inferential statistics (person correlation coefficient and t-test).Results: Results of the study indicates that there is a significant comparative difference between parents' awarenesstowards adolescents' violence control in the study and control groups through the pre-test, post-test-Ι and post-test-ΙΙ.(after 3 to 4 weeks of post-test, for these results program is successful and can be considered as an effective means toincrease parents' awareness.Recommendations: The study recommended that such program can be implemented in form of sessions for parents ofadolescents in schools or reformation of juveniles to increase their awareness.